STUDI EMPIRIS EDUKASI MANAJEMEN BENCANA TANAH LONGSOR DI KABUPATEN BANJARNEGARA - Lustono, Lustono; Bahtyar, Khafid Nur; Saputra, Andi Wahyu (Medikonis, 2024)
ABSTRACT Landslides are a serious threat to the community in Banjarnegara Regency, Indonesia. The mountainous topography is one of the main factors contributing to the occurrence of landslides. To reduce the impact of this disaster, an effective approach through education related to landslide disaster management is crucially needed. This research aims to investigate the results of education on landslide disaster management in Banjarnegara Regency. This research uses interview methods with community leaders, village officials, and government representatives who are related to the experience, perception, and actions concerning the implemented education program in Banjarnegara Regency. The analysis method involves steps such as data transcription, identification of themes, and analysis to understand the messages conveyed in the data. The results of the research show that there has been an increase in knowledge and awareness of the community after participating in the education program. The informants demonstrate a better understanding of the dangers of landslides, prevention measures, and emergency actions to be taken during and after a landslide disaster.